POTENSI REMPAH-REMPAH TRADISIONAL SEBAGAI SUMBER ANTIOKSIDAN ALAMI UNTUK BAHAN BAKU PANGAN FUNGSIONAL): (The Potential of Traditional Spices as a Source of Natural Antioxidants for Functional Food Raw Materials) - Andi Widya Helmalia; Putrid Putrid; Andi Dirpan (jurnal1, 2019)
Along with the development of an increasingly advanced era, people increasingly consume fast food or junk food. This is what causes the emergence of degenerative diseases based on lifestyle. So that comes the functional food concept. Functional food is food or drink that has physiological functions on the body. For example, consuming antioxidants to counteract free radicals that occur in the body. This source of natural antioxidants can come from various types of plants such as fruits, vegetables, spices, tea, or enzymes and proteins. As we have seen, Indonesia is a country rich in spices. This spice can be used as a source of natural antioxidants that have many benefits for the body. The types of spices in Indonesia are ginger, turmeric, cinnamon, secang, and andaliman. Ginger contains antioxidant compounds, namely methyl ester, 9-octadeconic and nortraselogenin. The study of turmeric and acid powder extracts had a comparison of 55% turmeric extract and 45% acid leaf extract resulting in a value of 4.844%. Cinnamon can be an antioxidant source because it contains many compounds such as eugenol, safrole, cinnamaldehyde, tannin, and calcium oxalate. The active components contained in the cage are flavonoids. Andaliman fruit has the potential as an antioxidant and a-glucosidase inhibitor.